The Relationship Between School Culture And Pro Environmental Behavior Among Senior High School Students In Yogyakarta - Ahmad Chandra Jaya; Nur Azizah; Muhammad Fikri Aulia (Journal of Innovation in Educational and Cultural Research, 2024)
Currently, students are expected to have the ability to solve environmental problems, especially in everyday life, which is known as pro-environmental behavior or action. One strategy in teaching students' problem-solving skills is to increase pro-environmental behavior. This study aims to obtain empirical data or facts that are actually true and reliable regarding the relationship between school culture and pro environmental behavior in students. This research is motivated by the existence of a school culture that is useful for strengthening pro environmental behavior for students. The method used in this research is quantitative method with correlational research design. The sample in this study amounted to 30 students on the grounds that the distribution of values would be closer to the normal curve. The results of the study have a positive correlation level of .976 with very strong correlation results. Thus, the conclusion of this study is that there is a significant relationship between school culture and pro environmental behavior with a positive correlation. The implication of this study is that it can be used as a reference material in developing school culture to improve pro environmental behavior.